Capital Structure Impact on Classical and Islamic Banks Profitability: Evidence from Moroccan Context - Mohamed Lachaari; Mustapha Benmahane (International Journal of Islamic Khazanah, 2022)
The focus of this paper is to clarify how capital structure affects Moroccan banks profitability and to answer the question about the impact of the participative banks introducing into the Moroccan banking system on bank’s profitability. Thus, the sample concerns, on one hand, data from 2007 until 2018 about the most important Moroccan banks regarding their market share and the collected data is analyzed using OLS regression. Therefore, in this work we introduce the participative banks data into the model to see how it behaves. Our findings show an increasing relationship between banks profitability and debt ratio with acceptable indicators. Therefore, leverage would be preferable to equity under study’s specific conditions, which means that bank’s profitability is generally related to bank’s capital structure. Although, when participative banks data are included we observe capital structure has no important effect on banks profitability in spite of the fact that the model is still significant.